Ketamine-induced peripheral analgesia in rats - Bai Li; Zhao Zhi-Qi (Acta Pharmacologica Sinica, 2016)
AIM: To examine whether ketamine may directly act at peripheral nociceptors to produce analgesia. METHODS: Wistar rats were anesthetized with urethane. As a nociceptive flexion reflex (FR), C responses from the posterior biceps semitendinosus (PBST) muscle was evoked by electrical stimulation (2 ms, 80 V, 2-3 pulses, 0.5 Hz) via a pair of stainless steel needles inserted subcutaneously applied to the two toes of ipsilateral hindpw. RESULTS: Subcutaneous injection of ketamine (36 mmol.L-1, 5 microL) into the ipsilateral hindpaw produced an inhibition of C responses. At 9 min after application of ketamine, injection of naloxone (1%, 5 microL) into the same area annulled ketamine-induced inhibition. CONCLUSION: Ketamine as a dissociate anesthetic acts on peripheral nociceptors to produce analgesia, which is related to activity of peripheral opioid receptors.